PARKING RETRIBUTION ON THE SIDE OF THE ROAD TOWARDS THE IMPROVEMENT OF LOCALLY-GENERATED REVENUE OF NGAWI REGENCY - Sarjiyati Sarjiyati; Krista Yitawati; Zainal Arifin (Legal Standing : Jurnal Ilmu Hukum, 2018)
The aims of this study are to know and to analyze the contribution of parking retribution on the side of the road towards the improvement of locally-generated revenue in Ngawi Regency. In addition, it is to measure the whether or not the parking retribution on the side of the road in Ngawi is in accordance with the regional regulation number 23/2011 on parking retribution on the side of the road. This study use empirical juridical research design.   The types of data used in this study are primary and secondary data. These data are obtained directly through interview, observation, and documentation. The data is analyzed qualitatively and quantitatively. Then, it is presented in a descriptive way. The result showed that the contribution of parking retribution on the side of the road towards the improvement of locally-generated revenue in Ngawi Regency in 2013-2017 is decreased. The biggest contribution was in 2013 with 4.69%, while the lowest contribution is in 2016 with 2.104%. Nowadays, the implementation of parking service in Ngawi Regency is not in accoradance with the regulation number 23/2011 concerning parking retribution on the side of the road.